BIOSYNTHESIZED ZnO NANOPARTICLES FROM Rumex nepalensis (SPRENG.) PLANT EXTRACT SERVE AS EFFICIENT CATALYSTS FOR THE AQUEOUS SYNTHESIS OF 4H-ISOXAZOL-5-ONE DERIVATIVES - P. PAWAR , ABHIMANYU; J. MUNGOLE , ARVIND; S. NAKTODE, KISHOR (The Bioscan, 2023)
In this study, the biosynthesis of ZnO nanoparticles was accomplished using an aqueous extract derived from Rumex nepalensis (Spreng) plant. The application of these biosynthesized ZnO nanoparticles as catalysts was investigated for the synthesis of biologically active 4H-isoxazol-5-one-based heterocycles. This was achieved through a one-pot three-component reaction involving hydroxylamine hydrochloride, aryl or heteroaryl aldehydes, and ethyl acetoacetate. The reactions were conducted at room temperature in aqueous medium, employing a 10 mol% loading of the biosynthesized ZnO catalyst. The structure of the biosynthesized ZnO was characterized using X-ray diffraction and scanning electron microscopy analyses. The resulting condensation process using biosynthesized ZnO nanoparticles exhibited environmentally friendly features such as safety, high yield of products, good atom efficiency, low cost, mild reaction conditions, minimal waste generation, avoidance of hazardous organic solvents, catalyst recoverability, energy efficiency, and facile workup.